Writing Disaster: Trauma, Memory, and History in Edwidge Danticat’s The Farming of Bones - Munro, Martin (Ethnologies, 2006)
This essay deals with the question of trauma in Haitian writing, and specifically with Edwidge Danticat’s novel The Farming of Bones. Drawing on a wide range of theorists, and undertaking a close reading of the novel, the essay suggests that the Haitian experience of trauma is different in many ways to that of other Caribbean islands. In particular, it is argued that the fragmented experience of Haitian history cannot be easily recuperated into contemporary celebratory theories of Caribbean hybridity and creolization, and must be understood within its own context and on its own terms.